Two new nematode species from Saldanha Bay, South Africa: Perepsilonema benguelae sp. nov. and Leptepsilonema saldanhae sp. nov. (Desmodorida, Epsilonematidae) - Hendricks, Martin G. J.; Gibbons, Mark J. (Zootaxa, 2010)
Perepsilonema benguelae sp. nov. and Leptepsilonema saldanhae sp. nov. are described and illustrated from coarse sand sediments in Saldanha Bay, along the west coast of South Africa. Perepsilonema benguelae sp. nov. is characterised by a large swollen body in the genital region, the annuli are not clearly orientated into anteriorly and posteriorly directed margins and copulatory thorns are restricted to three pairs in the precloacal region. In Leptepsilonema saldanhae sp. nov. the somatic setae in the pharyngeal region are very long and the first ambulatory setae of the external subventral row are short. Other distinguishing features include the shape of the amphidial fovea and the copulatory apparatus, and the presence of six ventro-lateral copulatory thorns around the cloaca. These descriptions are the first for the family Epsilonematidae from the west coast of South Africa.